Nonlinear control systems design : selected papers from the IFAC Symposium, Capri, Italy, 14-16 June 1989 - Isidori, Alberto (IFAC symposia series ;, 1990)
In the last two decades, the development of specific methodologies for the control of systems described by nonlinear mathematical models has attracted an ever increasing interest. New breakthroughs have occurred which have aided the design of nonlinear control systems. However there are still limitations which must be understood, some of which were addressed at the IFAC Symposium in Capri. The emphasis was on the methodological developments, although a number of the papers were concerned with the presentation of applications of nonlinear design philosophies to actual control problems in chemic.